Significant Declines in Juvenile-onset Recurrent Respiratory Papillomatosis Following Human Papillomavirus (HPV) Vaccine Introduction in the United States. (23rd February 2021) - Meites, Elissa; Stone, Laura; Amiling, Raiza; Singh, Vidisha; Unger, Elizabeth R; Derkay, Craig S; Markowitz, Lauri E
Abstract: Background: Juvenile-onset recurrent respiratory papillomatosis (JORRP) is a rare and serious disease caused by human papillomavirus (HPV) presumably acquired during vaginal delivery. HPV vaccination of females through age 26 years, recommended in the United States since 2006, can prevent HPV transmission. We assessed trends in JORRP cases before and after HPV vaccine introduction in the United States. Methods: Case-patients were identified from 26 pediatric otolaryngology centers in 23 U.S. states. Demographics and clinical history were abstracted from medical records. Case-patients were grouped by year of birth, and birth-cohort incidences were calculated using number of births from either national or state-level natality data from the 23 states. We calculated incidence rate ratios (IRR) and 95% confidence intervals (CI) in 2-year intervals. Results: We identified 576 U.S. JORRP case-patients born in 2004–2013. Median age at diagnosis was 3.4 years (interquartile range: 1.9, 5.5). Number of identified JORRP case-patients declined from a baseline of 165 born in 2004–2005 to 36 born in 2012–2013. Incidence of JORRP per 100 000 births using national data declined from 2.0 cases in 2004–2005 to 0.5 cases in 2012–2013 (IRR = 0.2, 95% CI = .1–.4); incidence using state-level data declined from 2.9 cases in 2004–2005 to 0.7 cases in 2012–2013 (IRR = 0.2, 95% CI = .1–.4). Conclusions: Over a decade, numbers of JORRP case-patients and incidences declined significantly. Incidences calculated using national denominator data are likely underestimates; those calculated using state-level denominator data could be overestimates. These declines are most likely due to HPV vaccination. Increasing vaccination uptake could lead to elimination of this HPV-related disease. Abstract : Prospective and retrospective data (2008–2017) from pediatric otolaryngology practices in 23 US states showed numbers of children with juvenile-onset recurrent respiratory papillomatosis (JORRP) and JORRP incidence have declined significantly. Declines are most likely due to human papillomavirus (HPV) vaccination.